PENGARUH PENGUNGKAPAN CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK DENGAN CORPORATE SOSIAL RESPONSIBILITY SEBAGAI VARIABEL MEDIASI - Husaini; Nikmah; Kiki Rezki Amanda (UNIB Press, 2023)
This hresearch is motivated by the problem of corporate tax avoidance which is increasing every year. The purpose of this study was to determine the effect of Corporate Governance (CG) disclosure on tax avoidance with Corporate Social Responsibility as a mediating variable. The sample in this study is 35 companies in Indonesia that present annual reports and sustainability reports that are included in the Asia Sustainability Reporting Rating (ASR Rating) in 2018 and 2019. The test analysis uses multiple regression analysis using SPSS 23. The research method used is quantitative research. research shows that corporate governance has an effect on tax avoidance. However, Corporate social responsibility is not able to mediate the influence of Corporate Governance on Tax Avoidance.